Exploring the potential transdiagnostic treatment effects of Chinese herbal medicine and acupuncture on insomnia disorder comorbid with chronic pain: A scoping review - Yan Ling Kwok; Ran Wang; Hiu To Tang; Siyu Chen; Albert Yeung; Zhaoxiang Bian; Danny J. Yu (Integrative Medicine Research)
Background: Over 20 % of adults with insomnia disorder also experience chronic pain, termed insomnia disorder comorbid with chronic pain (ICCP), increasing risks for physical and mental diseases. Current treatments like cognitive behavioral therapy for insomnia show inconsistent pain relief, and non-opioid analgesics may exacerbate insomnia, underscoring the need for alternative approaches. Chinese herbal medicine (CHM) and acupuncture, guided by traditional Chinese medicine, may offer transdiagnostic benefits for ICCP, but a comprehensive review is lacking. This scoping review evaluates their therapeutic effects and mechanisms for ICCP. Methods: PubMed, Wanfang, ClinicalTrials.gov and Google Scholar were searched up to December 31, 2024, for randomized controlled trials (RCTs) involving adults (≥18 years) with Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition-defined insomnia and the International Association for the Study of Pain-defined chronic pain, treated with CHM or acupuncture. Effect sizes (modified Cohen’s d) assessed efficacy of interventions, and the Cochrane Risk of Bias 2 tool evaluated the risk of bias. Results: Six RCTs (487 participants) were included. CHM (modified Guipi decoction) showed medium to large effects for insomnia (d = 0.70–1.17) and pain (d = 0.67–1.42) versus diazepam/estazolam. Acupuncture had medium to large effects for insomnia (d = 0.64–0.99) and pain (d = 0.80–1.33) compared to treatment as usual. Combined CHM (Da Huoluo capsules) and acupuncture showed medium effects (d = 0.72 for insomnia; d = 0.57 for pain) versus multi-medications/traction. Most studies (83.33 %) had high risk of bias. Conclusion: CHM and acupuncture show promise for ICCP management, but high risk of bias warrants cautious interpretation and further high-quality RCTs.